THE EVALUATION AND THE REHABILITATIVE APPROACH IN ARTHROGRYPOSIS - Figen Ardıç; Z. Rezan Yorgancıoğlu; Yaşar Kahraman; Gülin Fındıkoğlu (Archives of Rheumatology, 2003)
Amyloplasia or classic arthrogryposis is the most common form of arthrogryposis multiplex congenita (AMC). Characteristically congenital contractures are seen in upper and/or lower extremity, normal intelligence, and absence of major systemic malformation and chromosomal abnormality are the main features of classic AMC. We have reviewed diagnostic and rehabilitative approaches of AMC for a case of 8-months old baby with classic AMC.